2022
DOI: 10.1093/icesjms/fsac013
|View full text |Cite
|
Sign up to set email alerts
|

Calanus finmarchicus basin scale life history traits and role in community carbon turnover during spring

Abstract: The copepod Calanus finmarchicus was investigated in four Subpolar Basins, Labrador, Irminger, Iceland, and Norwegian Seas, during spring, covering the time of ascent, grazing, and initiation of reproduction in the area. Lipid content, spawning activity, and stage composition and vital rates, such as egg and faecal pellet production were measured and linked to environmental parameters. Specific egg- and faecal pellet production rates varied with diatom biomass and were negatively correlated with temperature. C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 61 publications
1
1
0
Order By: Relevance
“…in good agreement with the published range for C. finmarchicus (Hirche et al, 1997;Mayor et al, 2006;Møller et al, 2016;Jońasdottir et al, 2022). The observed rates did not correlate with any measure of ingested food quantity or prey type.…”
Section: Egg Productionsupporting
confidence: 90%
See 1 more Smart Citation
“…in good agreement with the published range for C. finmarchicus (Hirche et al, 1997;Mayor et al, 2006;Møller et al, 2016;Jońasdottir et al, 2022). The observed rates did not correlate with any measure of ingested food quantity or prey type.…”
Section: Egg Productionsupporting
confidence: 90%
“…This either suggests that the link between recent feeding history and egg production rate is weak, or that the rate at which eggs are produced is not directly limited by the available food. However, many studies have found a strong link between food quantity and egg production rate (Marshall and Orr, 1958;Hirche, 1990;Ohman and Runge, 1994;Hirche et al, 1997;Harris et al, 2000;Hirst and Bunker, 2003;Jońasdottir et al, 2022). Two of these studies were conducted in the Arctic, but the animals were either kept under identical feeding conditions for some time before experimentation (Hirche et al, 1997), or their eggs were only counted after 48 hours (Hirche, 1990), rather than 24 hours used herein, to allow for a longer spawning interval.…”
Section: Egg Productionmentioning
confidence: 99%
“…Over this period a rise in Chl‐ a concentrations were noted, by approximately 0.25 mg m −3 (equivalent to 10.5 mg m −2 over a 42 m depth). By using a regional average C:Chl‐a ratio of 61 (Jónasdóttir et al., 2022; Roy et al., 2017) and a C:N ratio of 6.6 (Redfield et al., 1963) this increase in phytoplankton biomass was equivalent to a nitrate utilization of 0.2 μmol kg −1 . This marginal change in the nitrate time‐series was minor compared to the vertical nitrate flux.…”
Section: Resultsmentioning
confidence: 99%
“…copepods play a pivotal role as they dominate the planktonic grazer biomass, are exceptionally adapted to polar regions and are sensitive to various stressors and chemical pollutants (Karnovsky et al., 2010 ; Kosobokova & Hirche, 2009 ; Sørensen et al., 2023 ). They serve as the link between primary production and higher trophic levels and contribute significantly to the carbon export and recycling of nutrients to the deep sea (Jónasdóttir et al., 2015 , 2022 ; Steinberg & Landry, 2017 ). The exposure to stressors can adversely affect their life cycle and could thus decrease the efficiency of the marine food web.…”
Section: Introductionmentioning
confidence: 99%